Supracondylar femoral rotation osteotomy affects frontal hip kinetics in children with bilateral cerebral palsy - Thielen, Mirjam; Wolf, Sebastian Immanuel; Klotz, Matthias C. M.; Geisbüsch, Andreas; Putz, Cornelia; Krautwurst, Britta; Dreher, Thomas (Developmental medicine and child neurology, 2019)
Aim To evaluate the influence of supracondylar femoral derotation osteotomy (FDO) on hip abduction muscle force and frontal hip moments in children with bilateral cerebral palsy. Method For this retrospective cohort study 79 children (36 females, 43 males; mean age at surgery 11y [SD 3y]; range 4-17y) with bilateral cerebral palsy and preoperatively and 1-year postoperatively documented frontal hip moments who received supracondylar FDO in 134 limbs were included. The control group consisted of eight children (two females, six males; mean age 11y [SD 4y]; range 5-17y) who received single-event multi-level surgery without FDO. Results Hip joint impulse (p<0.001) and the first peak of frontal hip moments (p=0.003) increased, whereas the second peak decreased (p<0.001) from preoperatively to postoperatively. Hip abductor strength improved (p=0.001) from preoperatively to postoperatively. Interpretation Despite the compensatory mechanism, frontal hip moments are decreased preoperatively. Supracondylar FDO results in increased frontal hip moments. Changes in anteversion directly influence hip kinetics, although no direct change of the proximal bony geometry is performed. What this paper adds Internal rotation gait cannot fully restore the frontal hip moment. Supracondylar femoral derotation osteotomy (FDO) influences frontal hip kinetics in children with bilateral cerebral palsy. Supracondylar FDO changes the curve progression of frontal hip moments. Supracondylar FDO restores the hip abductor moment arm. Supracondylar FDO leads to an increase in hip abductor muscle force.
First published: 25 September 2018
Gesehen am 06.08.2019